T Levels and indicators measuring the development of urban society and its explanatory theories: Sociology of urbanization in Algerian - Belaid , Mohammed (Social Empowerment Journal, 2023)
This research paper aims to identify the most important indicators for measuring the level of urbanization within the city and its relevance to the development and preparation of urbanization within the urban field. urbanization to the reality of this change resulting from the development of many of these levels, which greatly affected its internal and external structure and contributed to the transition from a stage characterized by limited living and its urban pattern to another stage characterized by an accelerated lifestyle that had repercussions on the difference in cultures, urban variables and the social conditions in which they lived. Which requires controlling these urban levels and understanding the social, economic and urban changes that they cause within any city